Multiple Integral Inequalities for Schur Convex Functions on Symmetric and Convex Bodies (Analysis in Theory and Applications, 2023)
In this paper, by making use of Divergence theorem for multiple integrals,we establish some integral inequalities for Schur convex functions defined on bodies $B⊂\mathbb{R}^n$ that are symmetric, convex and have nonempty interiors. Examples for threedimensional balls are also provided.
Keywords: Schur convex functions; multiple integral inequalities.